2005
DOI: 10.1007/s11373-004-8168-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitogen-activated protein kinase pathway in reactive oxygen species-mediated endothelin-1-induced β-myosin heavy chain gene expression and cardiomyocyte hypertrophy

Abstract: Endothelin-1 (ET-1) has been found to increase cardiac beta-myosin heavy chain (beta-MyHC) gene expression and induce hypertrophy in cardiomyocytes. ET-1 has been demonstrated to increase intracellular reactive oxygen species (ROS) in cardiomyocytes. The exact molecular mechanism by which ROS regulate ET-1-induced beta-MyHC gene expression and hypertrophy in cardiomyocytes, however, has not yet been fully described. We aim to elucidate the molecular regulatory mechanism of ROS on ET-1-induced beta-MyHC gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 26 publications
2
31
0
2
Order By: Relevance
“…The activity of the redox system is mediated by MAPK which closely links with ET-1 [41] . Upregulation of mRNA of PKCε and pPKCε protein in response to β-stimulation has been previously found [15] and is also confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the redox system is mediated by MAPK which closely links with ET-1 [41] . Upregulation of mRNA of PKCε and pPKCε protein in response to β-stimulation has been previously found [15] and is also confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Through excessive oxidative stress and activation of mitogen-activated protein kinase, tyrosine kinase pathways and nuclear factor kB, ET-1 stimulates VSMC proliferation and inflammation, all implicated in the thickening of vascular wall, vascular remodelling and in the development of atherosclerosis and end-organ damage. 8,26 As we have shown recently, there exists an inverse correlation between plasma ET-1 level and FRAP in treated hypertensive subjects. 17 In this study, we developed this observation, and demonstrated that inclusion of FRAP in the multivariate regression model as one of the independent variables changed the relationship between ET-1 and CCA-IMT, and not ET-1, but FRAP, apart from age, SBP and HbA1c level independently inversely influenced CCA-IMT.…”
Section: Discussionmentioning
confidence: 86%
“…1,4,6 Through the activation of mitogen-activated protein kinase, it stimulates cardiomyocyte hypertrophy. 7,8 Taken together, these findings suggest that ET-1 has a substantial role in the development of atherosclerosis and endorgan damage in patients with hypertension and diabetes. 4,6 The contribution of endogenous ET-1 to cardiovascular regulation and pathogenesis and disease progression has been confirmed by the effects of ET receptor antagonists.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…While Xia et al (2006) indicated that durasentan, an ETA-R inhibitor, downregulates NF-κB expression in heart ventricles. Furthermore, administration of BQ485, ETA-R blocker, reduced ET-1 induced activation of Ras-Raf-MAPK cellular pathway in myocytes inhibiting inflammatory process and cellular damage (Cheng et al 2005).…”
Section: Discussionmentioning
confidence: 92%